Design of Wrist Rehabilitation Mechanism and Research on Impedance Control - Guo Ce; Chen Yu; Wang Huaiyang; Kan Yanpeng; Meng Qingyang; Lu Mengchen (Jixie chuandong)
In order to better assist patients with wrist injuries in rehabilitation, a wrist rehabilitation trainer was designed. Firstly, the structure of the rehabilitation trainer was designed based on the biological motion mechanism of the wrist joint and the bionic principle, and the design of the flexible compensation joint of the wrist joint was added. After that, the kinematic model of the wrist joint was established based on the flexible compensated joint, and the working space of the trainer was obtained. Then, the virtual prototype platform was built, and the joint drive impedance controller was designed for joint simulation test. The influence of friction parameters, damping parameters and human-machine contact load on the impedance control performance was analyzed through the simulation test to verify that the joint control can be realized, and the working space of the compensated joint was compared and analyzed to verify the rationality and feasibility of the structural design of the trainer and to provide a theoretical basis for the production of the next physical prototype.